(untitled) (Journal of the College of Basic Education, 2022)
This research aspires to raise an issue that we believe occupies a privileged position in the Andalusian civilizational giving, related to the tolerance that prevailed in Islamic Andalusia towards the Jews and the Christian dhimmis, who constituted an important segment of the Andalusian society.We have no doubt that raising the issue of tolerance between different peoples and religions in the academic field is justified, in the midst of the struggle of globalization and the domination of one pole and in an ideological atmosphere dominated by the saying of the end of history, and pushed by the arrogance of the clash of civilizations to poverty and misery, and to follow the methods of terrorism and hatred of the other; We need the Andalusian, tolerant, coexistent civilized view; To dedicate the philosophy of love, and to train minds on the culture of integration and acceptance of the other,